Self-Acquired Knowledge is of Great Personal Importance - Fayzieva Gulzoda Ulugbekovna (Scholars Digest Publishing, 2023)
Self-management is another skill that is important in checking a student’s work independently for errors, at a pre-teacher level of control. Self-testing can be seen as synonymous with self-testing. Introspection and self-management are very important, especially when there is no direct contact with the teacher.
Keywords: A person with critical abilities, overcoming stereotypes, critical appraisal, associative method, learning trajectory, self-management, distance learning opportunities, distance learning gaps, distance learning perspectives.